CAUSALITY DYNAMICS OF CORRUPTION AND ECONOMIC GROWTH IN AN EMERGING ECONOMY - B. W. Mazviona (Стратегические решения и риск-менеджмент, 2022)
Leveraging on the Ibrahim Index of African Governance (IIAG) and economic growth rate data from the World Bank (WB), this study employs a robust VAR time series methodology in delineating the relationship between corruption and economic growth in Zimbabwe. Noting the worsening corruption levels coupled with a grim economic performance, this study informs policy for the new political administration keen to fight corruption. The study affirms a unidirectional causality flowing from corruption to economic growth and a negative impulse response. To increase the fortunes of the economy in the future, current action to ‘stop’ corruption is obligatory.